Analisis Studi Komparatif Penerimaan Zakat Produktif Dalam Perkembangan Usaha Mikro Mustahik (Studi Kasus LAZ OPSEZI Kota Jambi Dan BAZNAS Kota Jambi) - Lala Fitriana; A. Tarmizi; Agusriandi Agusriandi (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2023)
This study aims to determine the differences in receipt of productive zakat LAZ OPSESI Jambi city and receipt of productive zakat BAZNAS Jambi city in the development of mustahik micro enterprises. Primary data collection method used is to use a media questionnaire. The sample of this research is the number of mustahik LAZ OPSESI and BAZNAS, totaling 100 respondents. This research method is quantitative with multiple linear regression analysis as its analysis. The results of the research show that the variable value of t count (2.521) > t table (1.985) with a significance value of 0.013 <0.05. This means that it can be concluded that Ha is accepted and Ho is rejected which states that there is a significant difference between the variable LAZ OPSEZI Productive Zakat Receipt in Jambi City and the Mustahik Micro Business Development variable. It is known from the results of the t test, it is found that the variable influences the value of t count (3.906) > t table (1.985) with a significance value of 0.000 <0.05. This means that it can be concluded that Ha is accepted and Ho is rejected which states that there is a significant difference between the Jambi City BAZNAS Productive Zakat Receipt variable and the Mustahik Micro Business Development variable. Based on the results of the F test, the calculated F value is 25.905 and the F table is 2.70 ( 25.905 > 2.70), and a significant value of 0.000 where p <0.05, so the F test results are 0.000 <0.05, it can be concluded that Ha is accepted and Ho is rejected, which means that there is a significant difference between the variables of Productive Zakat Receipts Jambi City LAZ OPSEZI (X1), Jambi City BAZNAS Productive Zakat Receipts (X2), in Mustahik Micro Business Development (Y).